What’s in Your Tweets? I Know Who You Supported in the UK 2010 General Election - Boutet, Antoine; Kim, Hyoungshick; Yoneki, Eiko (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Nowadays, the use of social media such as Twitter is necessary to monitor trends of people on political issues. As a case study, we collected the main stream of Twitter related to the 2010 UK general election during the associated period. We analyse the characteristics of the three main parties in the election. Also, we propose a simple and practical algorithm to identify the political leaning of users using the amount of Twitter messages which seem related to political parties. The experimental results showed that the best-performing classification method – which uses the number of Twitter messages referring to a particular political party – achieved about 86% classification accuracy without any training phase.